Pengembangan Perilaku Religius di Pondok Pesantren Dalam Membentuk Karakter Santri - Rohmah, Khoiru; Syarif, Nasrul (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
Behavior is an activity or activity of the organism (living thing) concerned when viewed from a biological perspective. Character is something that is found in individuals that characterizes individual personalities that are different from others in the form of attitudes, thoughts, and actions. An institution that houses students to study. Based on this background, the researcher asks the following research questions (1) how is the implementation of the development of religious behavior in Islamic boarding schools in shaping the character of students? (2) how are the results of the development of religious behavior in Islamic boarding schools in shaping the character of students? This study uses a descriptive qualitative approach to describe and summarize various conditions. Data collected by using the method of observation, interviews (interviews), and documentation. This final stage uses the validity of the findings with Triangulation, Reference Materials. From the results of this study: (1) The implementation or application is seen in two parts including: the stimulus or encouragement given by the teacher and administrator will have an impact on the students, and the response given by the student is seen from the stimulus or encouragement that has been given from the teacher and administrator. (2) The results in shaping the character of students are obtained from seeing two reinforcements, including positive reinforcement given by students to maintain positive behavior, and negative reinforcement this is given so that it becomes a reflection so that they do not make mistakes again.